How the Behavior Change Content of a Nationally Implemented Digital Diabetes Prevention Program Is Understood and Used by Participants: Qualitative Study of Fidelity of Receipt and Enactment - Lisa M Miles; Rhiannon E Hawkes; David P French (JMIR Publications, 2023)
BackgroundThe National Health Service Digital Diabetes Prevention Programme (NHS-DDPP) is a program for adults in England at risk of developing type 2 diabetes mellitus (T2DM). It is based on NHS England specifications that stipulate specific behavior change techniques (BCTs), that is, active ingredients to produce behavior change to target diet and physical activity. Now rolled out nationally, the NHS-DDPP is being delivered by 4 independent providers as a 9-month intervention via apps, educational material, and remote health coaching. To optimize effectiveness, participants need to be able to understand and use behavior change content (eg, goal setting and problem solving) of an intervention delivered to them digitally. Previous research has shown that people benefit from support to aid the understanding and use of BCTs. ObjectiveThe objectives of this qualitative study were to evaluate how participants in the NHS-DDPP understand and use BCT content, investigate how participants describe the role of health coaches in supporting their behavior change, and examine how the understanding and use of behavior change content of the NHS-DDPP varies across providers. MethodsIn total, 45 service users were interviewed twice by telephone at 2 to 4 months into, and at the end of, the program. Topics included participants' understanding and use of key BCTs to support self-regulation (eg, goal setting) and the support they received via the program. Transcripts were analyzed thematically, informed by the framework method. ResultsParticipants described their understanding and use of some behavior change content of the program as straightforward: use of BCTs (eg, self-monitoring of behavior) delivered digitally via provider apps. Participants valued the role of health coaches in supporting their behavior change through the emotional support they offered and their direct role in delivery and application of some BCTs (eg, problem solving) to their specific circumstances. Participants expressed frustration over the lack of monitoring or feedback regarding their T2DM risk within the program. Variations in the understanding and use of behavior change content of the NHS-DDPP were present across provider programs. ConclusionsHealth coaches' support in delivery of key components of the program seems to be pivotal. To improve the understanding and use of BCTs in digital interventions, it is important to consider routes of delivery that offer additional interactive human support. Understanding of some self-regulatory BCTs may benefit from this support more than others; thus, identifying the optimal mode of delivery for behavior change content is a priority for future research. The NHS-DDPP could be improved by explicitly setting out the need for health coaches to support understanding of some self-regulatory BCT content such as problem solving in the service specification and amending the discharge process so that knowledge of any change in T2DM risk is available to participants.